The Effect of Illness Perception Promoting Dietary Focus Program on Illness Perception and Dietary Behaviors in Muslim Patients with Ischemic Heart Disease - Youdkong, Saichon; Muensri, Busara; Kritpracha, Charuwan (Princess of Naradhiwas University Journal, 2021)
This quasi-experimental research aimed to examine the effect of illness perception promoting with dietary focus program on illness perception and dietary behaviors in Muslim patients with ischemic heart disease. The sample comprised fifty purposively selected defined properties into the experimental on control group. Subjects in the control group received routine nursing care while those in the experimental group received the illness perception promotion with dietary focus program. The content validity of the program and all instruments were examined by three experts. The test-retest reliability of the B-IPQ was .83. The internal consistency reliability of the dietary behavior Questionnaire in Muslim patients yield a Cronbach s alpha coefficient of .70. The results revealed that: The mean score of illness perception and the mean score of dietary behavior in Muslim patients with ischemic heart disease in the experimental group after receiving illness representation promoting program was higher than that of the control group. This study showed that the illness perception promotion with dietary focus program can promote appropriate illness perception and dietary behaviors in Muslim patients with ischemic heart disease.